2011
DOI: 10.1007/s11010-011-0910-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of abca1-mediated efflux of cholesterol at the mouse blood–brain barrier

Abstract: We investigated the expression and function of Abca1 in wild-type C57BL/6, abca1(+/+), and abca1(-/-) mice brain capillaries forming the blood-brain barrier (BBB). We first demonstrated by quantitative RT-PCR and Western immunoblot that Abca1 was expressed and enriched in the wild-type mouse brain capillaries. In abca1(-/-) mice, we reported that the lack of Abca1 resulted in an 1.6-fold increase of the Abcg4 expression level compared to abca1(+/+) mice. Next, using the in situ brain perfusion technique, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…The cholesterol efflux is preferentially directed to the apical compartment (the blood side) and probably helps regulating the cerebral pool of cholesterol. Taken as a whole, these data strongly reinforce the hypothesis whereby the human BBB is involved in cholesterol homeostasis in the brain and the periphery [29,31,42,62]. Thus, we hypothesized that if the physiology of the BBB is altered (as in several murine models of AD [19][20][21]50]), bexarotene will have less effect on the brain's cholesterol metabolism.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The cholesterol efflux is preferentially directed to the apical compartment (the blood side) and probably helps regulating the cerebral pool of cholesterol. Taken as a whole, these data strongly reinforce the hypothesis whereby the human BBB is involved in cholesterol homeostasis in the brain and the periphery [29,31,42,62]. Thus, we hypothesized that if the physiology of the BBB is altered (as in several murine models of AD [19][20][21]50]), bexarotene will have less effect on the brain's cholesterol metabolism.…”
Section: Discussionsupporting
confidence: 68%
“…The brain endothelial cells (ECs) composing the BBB express several receptors, enzymes, and transporters that regulate brain homeostasis and composition of the milieu. We and others have demonstrated in vivo, in situ, and in vitro that ABCA1 is the major protagonist in the exchange of cholesterol between the brain and the blood [29][30][31]. The BBB also participates in the regulation of the brain pool of A␤ peptides in general and the re-entry of these peptides into the brain in particular [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 92%
“…The latter are important for the development, maturation, and maintenance of the properties of BBB [25,26]. In both in vitro and in vivo experiments, we and others have already demonstrated that BCECs and pericytes express LXR and their target genes (such as ABCA1) [21][22][23][27][28][29][30]. Given that as much as 6 to 7 mg of 24S-OH-chol crosses the BBB per 24 h [5], it is not surprising that this oxysterol increases the expression of ABCA1 and raises cholesterol release from BCECs to apoA-I and HDL particles [23,28,29].…”
Section: Introductionmentioning
confidence: 80%
“…Given that the BBB is thought to be involved in the complex process of brain cholesterol homeostasis [21][22][23] and in A␤ peptide exchanges between the blood and the brain (reviewed in [24]), it is essential to investigate the role of LXRs at the BBB level. The BBB is composed of brain capillary endothelial cells (BCECs), which are surrounded by pericytes.…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed in brain parenchymal cells [228], including the cerebrovascular endothelium [229, 230], and its brain endothelial expression levels can be pharmacologically upregulated by agonists of liver X receptors [229]. The experiments conducted in Abca1 −/− mice have shown that ABCA1 acts as a cholesterol efflux transporter at the BBB [230], but, unlike the BBB-associated low-density lipoprotein receptor-related protein 1 [231], it does not transport Aβ peptides from the brain into the blood [232]. This suggests the indirect effect of ABCA1 on Aβ deposition in the CNS.…”
Section: Tbi and The Transport Systems At The Bbbmentioning
confidence: 99%